Predictors of access to oral health services in Primary Health Care: Cross-sectional study (Research, Society and Development, 2023)
Access to oral health is a problem faced by many countries in the world as well as Brazil. The objective was to analyze the relationship between access to public dental services in Primary Health Care with individual and contextual factors. Cross-sectional study with a sample of adult subjects of both sexes, carried out in the city of São Paulo/SP from 2022 to 2023. The dependent variable was access, categorized into: scheduled access and unscheduled access. Descriptive analyzes were performed and later binary logistic regression models were estimated, with 95% CI and p